Response surface methodology to optimize aerial mapping electric UAV preliminary design and static stability analysis - Prytha Virgiawan Lesalli; Tresna Priyana Soemardi; Lilis Mariani (National Research and Innovation Agency, 2026)
This study addresses the need for efficient aerodynamic design in fixed-wing unmanned aerial vehicles (UAVs) for aerial mapping applications, where flight stability and cruising performance are critical. The research aims to optimize wing geometry parameters to achieve the desired cruising speed while minimizing drag and ensuring static stability. The methodology integrates conceptual and preliminary design approaches, followed by aerodynamic simulations using XFLR-5 with the vortex lattice methodology (VLM-2). Three design variables, winglet length, cant angle, and twist angle, are systematically varied, and the response surface method (RSM) is employed to model and optimize their effects on lift, drag, and airspeed. The optimization results indicate that the optimal configuration achieves a cruising speed of 16.8 m/s with improved lift characteristics (CL ≈ 0.48) and controlled drag (CD ≈ 0.022). Further analysis confirms that the optimized UAV satisfies longitudinal, lateral, and directional static stability criteria under various control surface deflections. In conclusion, the integration of RSM with aerodynamic simulation provides an effective and systematic framework for enhancing the UAV performance and stability, particularly in aerial mapping missions.